(untitled) (International Journal of Physiotherapy, 2025)
Background: Sensorimotor impairments caused by diabetic peripheral neuropathy (DPN) increase the risk of falls, make it challenging to move around, and impair balance. Physiotherapy interventions like Frenkel exercises (focused on voluntary motor control) and proprioceptive training (enhancing sensory feedback for stability) are used to address these deficits. This study compares their efficacy in improving balance, walking distance, and quality of life in individuals with DPN. Methods: 60 people with a diagnosis of DPN, ranging in age from 45 to 65, participated in a randomized controlled experiment. The participants were split into two groups: Group A (Frenkel exercises) and Group B (Proprioceptive training). Both groups underwent a 6-week intervention program, with outcomes assessed using the Mini-BESTest for balance, the 6-Minute Walk Test (6MWT) for walking distance, and the Diabetes Quality of Life (DQOL) scale. The statistical study used the Mann-Whitney U test and the Wilcoxon signed-rank test, with a significance level of p < 0.05. Results: Balance, mobility, and overall quality of life were all significantly enhanced by both treatments. However, Group B (proprioceptive training) showed significantly greater improvements in Mini-BESTest scores (p < 0.2), 6MWT performance (p < 0.07), and DQOL scores (p < 0.5) compared to Group A. Conclusion: The results indicate that proprioceptive training is superior to other interventions for improving postural stability, gait performance, and overall functioning in patients with DPN. These results support the integration of proprioceptive-based interventions into physiotherapy management for DPN patients.